Can participatory processes contribute to the sustainability of cultural and creative ecosystems? The case of the creative people and places (CPP) programme (England) - Lapucci, Giulia; Cerquetti, Mara; Boehm, Carola (Piccola Impresa / Small Business, 2025)
Purpose: Participatory and co-creative processes are now widespread in various sectors of our society, including the cultural and creative industries. The study aims to examine their contribution to the sustainability of cultural ecosystems and their integration within cultural policies. It explores best practices and emerging challenges, along with the impacts, both positive and negative, on members and communities, thus informing the development of sound cultural policies. Design/methodology/approach: Adopting the single case-study methodology, combining multiple data sources, including semi-structured interviews, observations, and documentary analysis, we discuss the case of Appetite, a project carried out in Stoke-on-Trent (UK) within the framework of Creative People and Places (CPP), a ten-year audience development programme targeting areas of England with below-average cultural engagement. Findings: The paper highlights good practices and critical issues in applying participatory methods to large-scale programmes in the cultural sector. It reveals that effective participatory processes can lead to greater community involvement and sustainability of cultural projects, but also highlights significant obstacles such as resource allocation and stakeholder alignment. Practical and social implication: The study emphasises the significance and intricacy of implementing participatory processes in contemporary cultural policy discourse, particularly in view of global calls for more inclusive and sustainable cultural development strategies. The study provides guidance to policymakers, cultural practitioners, and community leaders on the application of participatory practices, addressing benefits, potential challenges, and limitations. Originality of the study: This research contributes to the existing literature by offering a detailed qualitative analysis of a long-term, large-scale, participatory project in the UK cultural sector.